2020
DOI: 10.1186/s12860-020-00274-1
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial outer membrane protein SYNJ2BP interacts with the cell adhesion molecule TMIGD1 and can recruit it to mitochondria

Abstract: Background: Transmembrane and immunoglobulin domain-containing protein 1 (TMIGD1) is a recently identified cell adhesion molecule which is predominantly expressed by epithelial cells of the intestine and the kidney. Its expression is downregulated in both colon and renal cancer suggesting a tumor suppressive activity. The function of TMIGD1 at the cellular level is largely unclear. Published work suggests a protective role of TMIGD1 during oxidative stress in kidney epithelial cells, but the underlying molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 49 publications
(77 reference statements)
0
32
0
1
Order By: Relevance
“…The most significantly associated SNP fell within a 60Kb region within 14q24.2, overlapping with the 5’ region SYNJ2BP , the 3’ end of ADAM20 , and the entirety of ADAM21 . SYNJ2BP, synaptojanin 2 binding protein (OMIM ∗ 609411) is located on the outer membrane of the mitochondria ( Hartmann et al, 2020 ) and forms an unusual gene read-through product with neighboring gene COX16 (OMIM ∗ 618064) ( Figure 4 ), a known mitochondrial complex IV assembly factor ( Cerqua et al, 2018 ). Mitochondria play a vital role in brain function, and therefore this represents an interesting potential mechanism to further explore.…”
Section: Discussionmentioning
confidence: 99%
“…The most significantly associated SNP fell within a 60Kb region within 14q24.2, overlapping with the 5’ region SYNJ2BP , the 3’ end of ADAM20 , and the entirety of ADAM21 . SYNJ2BP, synaptojanin 2 binding protein (OMIM ∗ 609411) is located on the outer membrane of the mitochondria ( Hartmann et al, 2020 ) and forms an unusual gene read-through product with neighboring gene COX16 (OMIM ∗ 618064) ( Figure 4 ), a known mitochondrial complex IV assembly factor ( Cerqua et al, 2018 ). Mitochondria play a vital role in brain function, and therefore this represents an interesting potential mechanism to further explore.…”
Section: Discussionmentioning
confidence: 99%
“…TMIGD1 is predominantly expressed by epithelial cells of the kidney (Arafa et al , 2015; Hartmann et al , 2020) and of the small intestine (Cattaneo et al , 2011; Zabana et al , 2020). In two colon-derived cell lines, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…TMIGD1 constructs in pInducer21-Puro: hTMIGD1 full length (AA1-262).TMIGD1 constructs in pcDNA3 (Invitrogen): hTMIGD1 full length (AA1-262), hTMIGD1 lacking the PDZ domain binding motif (hTMIGD1/Δ5, AA 1-258), hTMIGD1 lacking the cytoplasmic domain (hTMIGD1/ΔCP, AA 1-241). Flag-tagged TMIGD1-EGFP constructs in pKE1079(Hartmann et al, 2020): EGFP-hTMIGD1 (AA 30-262, EGFP inserted between AA211 and AA212 of TMIGD1); EGFP-TMIGD1-JAM-A (NH 2 -TMIGD1-30-211-EGFP-JAM-A-231-299-COOH). GST-tagged TMIGD1 constructs in pGEX-4T-1 (GE Healthcare): GST-TMIGD1 (hTMIGD1 cytoplasmic tail (AA 242-262); GST-TMIGD1/Δ5: hTMIGD1 cytoplasmic tail lacking the PDZ domain binding motif (AA 242-257).…”
mentioning
confidence: 99%
“…BAP31 is also involved in the attenuated sepsis-mediated myocardial depression by melatonin [42]. Recent data have suggested that synaptojanin-2binding protein (SYNJ2BP) localized on the OMM interacts with ribosome-binding protein 1 (RRBP1), and once SYNJ2BP is overexpressed, the mitochondria-ER contacts dramatically increase [44].…”
Section: The Structural Composition Of the Mitochondria-associated Membranes (Mams)mentioning
confidence: 99%